WORKING IN GROUPS THROUGH TRAININGS AS A FACTOR IN THE SOCIALIZATION OF THE YOUNGER GENERATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the education system, the role of the teacher is great in the free, creative, independent thinking of students in the educational process and training activities. It is expedient to use two principles in the structure of education - independent work and its organization - the principle of systematic and consistent work of independent work. The historical experience of the institute in each period of social development shows that the task of education cannot be accomplished without a certain system.